2007
DOI: 10.1007/s00125-007-0834-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations between insulin resistance and TNF-α in plasma, skeletal muscle and adipose tissue in humans with and without type 2 diabetes

Abstract: Aims/hypothesis Clear evidence exists that TNF-α inhibits insulin signalling and thereby glucose uptake in myocytes and adipocytes. However, conflicting results exist with regard to the role of TNF-α in type 2 diabetes. Methods We obtained blood and biopsy samples from skeletal muscle and subcutaneous adipose tissue in patients with type 2 diabetes (n=96) and healthy controls matched for age, sex and BMI (n=103). Results Patients with type 2 diabetes had higher plasma levels of fasting insulin (p<0.0001) and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 42 publications
6
80
1
5
Order By: Relevance
“…Participants were carefully screened, and exclusion criteria were treatment with insulin, recent or ongoing infection, history of malignant disease, or treatment with anti-inflammatory drugs. Subjects and protocol have been previously described (21,22). Participants (n ϭ 199) were given both oral and written information about the experimental procedures before giving their written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were carefully screened, and exclusion criteria were treatment with insulin, recent or ongoing infection, history of malignant disease, or treatment with anti-inflammatory drugs. Subjects and protocol have been previously described (21,22). Participants (n ϭ 199) were given both oral and written information about the experimental procedures before giving their written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Mounting evidence suggests that TNF-␣ plays a direct role in the metabolic syndrome (284). Patients with type 2 diabetes demonstrate a high protein expression of TNF-␣ in skeletal muscle and increased TNF-␣ levels in plasma (286,363).…”
Section: Anti-inflammatory Effects Of Interleukin-6mentioning
confidence: 99%
“…103 TNF-a is a strong inducer of lipolysis 104 and data from rodents and humans support a role in the development of insulin resistance. [105][106][107] The latter, however, has been challenged by others 108 and although TNF-a levels are increased in obesity, 109,110 there is little direct release from abdominal subcutaneous adipose tissue in vivo. 111 Interestingly, in a similar set of studies it was found that abdominal subcutaneous adipose tissue releases the soluble TNF receptor type 1 and that its levels correlate with BMI.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%